Rancang Bangun Sistem Identifikasi Kelainan Conduct Disorder Pada Anak Menggunakan Metode Teorema Bayes - Cahyo P.D, Galih Satrio; Arfida, Septilia (Prosiding Seminar Nasional Darmajaya, 2017)
Conduct disorders or severe disruptive behaviors usually occur in children. Children dare to commit deviating behavior repeatedly. This behavioral disorder has not been noticed by most parents. Moreover, this disorder arises due to various factors e.g., social environments, family environments, genetic factors, and violence.A psychological test which was manually done was still used. However, it caused a lot of human errors. To conduct this test, it had to be computerized. Furthermore, the method used in this research was Bayes Theorem. The Bayes Theorem was a right theorem for calculating possible behavioral abnormality symptoms. Software development method of this research was a prototype method with communication, quick plan, modeling quick design, prototype construction, deployment, delivery, and feedback.This system was to identify behavioral abnormalities by using input variables e.g., ages, children, parents, environments, and behaviors. In addition, the output variable was the conduct disorder. This identification system is able to identify the conduct disorder quickly, precisely, and efficiently.Keywords: Conduct Disorder, Bayes Theorem, Identification System